Development of 3D hydrogels for axonal regeneration - Soares, Mariana Castro (2024)
Spinal cord injury (SCI) is a degenerative and limitative medical condition that has no definitive treatment. Axonal regeneration is a required event to improve the outcomes of this condition, but traditional methods do not offer effective solutions. Recent investigations involving regenerative medicine alternatives have emerged as a potential new treatment for SCI. Among various possibilities, hydrogels are a particular type of biomaterial that stand out due to their design versatility that can match a specific set of properties. Therefore, we studied the possibility to apply a platelet lysates-based hydrogel in the context of SCI, as a platform that could promote axonal regeneration. Our results show that the methacryloyl platelet lysates (PLMA) hydrogel is not optimal in terms of cellular adhesion, but its adhesive properties could be enhanced using a coating of poly-D-lysine (PDL). We next encapsulated cortical neurons inside the PLMA matrix. The results suggested that neurons would have a better adhesion when encapsulated, which is relevant in the perspective of using PLMA as a cell carrier. Lastly, we tested the possibility of the presence of other cells inducing neuronal development, namely the presence of adipose stem cells (ASCs) and glial cells (GCs). For ASCs, we observed that these cells offered support to neuronal cells and that had a positive effect in neurite outgrowth inside PLMA gels. However, for GCs this outcome was not verified and further optimizations are required to determine if they might be a good alternative. Overall, PLMA hydrogels could be used as a scaffold for axonal growth and a carrier for neural cells, and possibly offering a better outcome when combined with stem cells.